News Briefs. - Garber, Lee (Computer (00189162), 2013)
Topics include major vendors backing efforts designed to support secure software development, US efforts to curb patent trolls, two technologies that make it easier to access Wi-Fi systems, software vendor SAP's plan to recruit hundreds of people with autism during the next few years, Cray releasing an "inexpensive" supercomputer, and two masks that give users highly improved powers of sight and hearing.